Desenvolvimento de mapas táteis para o ensino de geografia: proposta cartográfica para o município de Bagé-RS - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This dissertation investigated the impact of tactile maps on Geography education, with a focus on including students with and without visual impairments. The study, qualitative, exploratory, and descriptive in nature, aimed to analyze the creation, usefulness, and applicability of tactile maps in the educational context, with an emphasis on the reality of the municipality of Bagé, in Rio Grande do Sul. The work was based on the principles of Tactile Cartography, seeking to overcome the traditionally visual approach to teaching Geography and promote inclusive and relevant learning for all students. To achieve its objectives, the research unfolded in different stages. First, a comprehensive bibliographic survey was carried out on the history of Bagé, its relevant geographical aspects, and Tactile Cartography as a tool for inclusion. Then, three tactile maps were produced representing the Geomorphology, the Hydrography, and the places of the city. Low-tech resources were used, such as EVA sheets, lollipop sticks, and textured cords, as well as high-tech resources, such as 3D printing and laser cutting. The process of creating the maps involved the careful selection of materials, the adaptation of cartographic elements to the tactile format, and the inclusion of captions in Braille and high relief. In addition, videos with audio description accessible by QR Codes were included. The application of the maps was carried out in classes of the 6th and 8th grades of Elementary School, involving students with and without visual impairments, aged between 11 and 15 years. The methodology included the elaboration and application of didactic sequences on Geomorphology and Hydrography, using the respective tactile maps as a central tool, and a geographic trail activity with the map of places. The activities involved exploring the maps, building models, and applying the concepts of spatial orientation. The analysis of the results, based on the theories of Piaget and Vygotsky, revealed the potential of tactile maps to stimulate learning, spatial understanding, social interaction, and the development of cognitive and sensory skills. The results demonstrated that tactile maps were effective in promoting inclusion and student learning. Students with and without visual impairments actively participated in the activities, exploring the geographic space in a concrete and relevant way. The research also highlighted the importance of teacher mediation and the adaptation of teaching resources to ensure accessibility and inclusion for all students. During the research, opportunities to improve tactile maps were identified. The use of contrasting colors in the symbols and the expansion and optimization of the contrast between the text and the background of the captions stand out. The dissertation concluded that Tactile Cartography is an effective pedagogical tool for teaching Geography, promoting inclusion and relevant learning for all students. Tactile maps, combined with teacher mediation and social interaction, enabled the exploration of geographic space in a concrete and sensory way, contributing to the development of spatial.
Keywords: Cartografia tátil; Ensino; Geografia; Inclusão; Aprendizagem; Tactile cartography; Teaching; Geography; Inclusion; Learning; CNPQ::CIENCIAS HUMANAS